New Perspectives on Roles of Alpha-Synuclein in Parkinson’s Disease - Zhang, Guoxin; Xia, Yun; Wan, Fang; Ma, Kai; Guo, Xingfang; Kou, Liang; Yin, Sijia; Han, Chao; Liu, Ling; Huang, Jinsha; Xiong, Nian; Wang, Tao (Frontiers in Aging Neuroscience, 2018)
Parkinson’s disease (PD) is one of the synucleinopathies spectrum of disorders typified by the presence of intraneuronal protein inclusions. It is primarily composed of misfolded and aggregated forms of alpha-synuclein (α-syn), the toxicity of which has been attributed to the transition from an α-helical conformation to a β-sheetrich structure that polymerizes to form toxic oligomers. This could spread and initiate the formation of “LB-like aggregates,” by transcellular mechanisms with seeding and subsequent permissive templating. This hypothesis postulates that α-syn is a prion-like pathological agent and responsible for the progression of Parkinson’s pathology. Moreover, the involvement of the inflammatory response in PD pathogenesis has been reported on the excessive microglial activation and production of pro-inflammatory cytokines. At last, we describe several treatment approaches that target the pathogenic α-syn protein, especially the oligomers, which are currently being tested in advanced animal experiments or are already in clinical trials. However, there are current challenges with therapies that target α-syn, for example, difficulties in identifying varying α-syn conformations within different individuals as well as both the cost and need of long-duration large trials.